Changes in Cytokeratin 18 during Neoadjuvant Chemotherapy of Breast Cancer: A Prospective Study - Danial Fazilat-Panah; Somaye Vakili Ahrari Roudi; Alireza Keramati; Azar Fanipakdel; Mohammad hadi Sadeghian; Fatemeh Homaei Shandiz; Soudabeh ShahidSales; Seyed Alireza Javadinia (Iranian Society of Pathology, 2020)
Background & Objective: Prediction of response to neoadjuvant treatment is an important part of treatment of patients with breast cancer. This study aimed to assess changes in serum levels of Cytokeratin 18 during neoadjuvant chemotherapy in patients with locally advanced breast cancer and its association with neoadjuvant treatments. Methods: This research was performed on newly diagnosed breast cancer patients referred to Omid Radiotherapy Center and radiotherapy and oncology departments of Emam Reza and Ghaem hospitals, in Mashhad, Iran. Serum levels of M30 and M65 fragments of Cytokeratin 18 were measured before and 24 hours after the first course of neoadjuvant chemotherapy. Changes in serum levels of Cytokeratin 18 and its fragments and their correlation with pathologic response were analyzed. Result: Pre- and post-chemotherapy levels of M30 were respectively 223.9±18.94 and 250.7±23.92 U/L (P=0.24). For M65, these levels were respectively 301.5±313.9 and 330.2±352.2 U/L (P=0.1). Changes in M30 level during chemotherapy in patients with and without pathologic complete response were -20±92.69 and 43.1±106.5, respectively (P=0.1). For M65, these changes were respectively -247±55 and 76±240 (P=0.1). Baseline levels of M30 and M65 had no relation with menopausal status, tumor grade, hormone receptor status, Ki67 expression, molecular subtype, and stage. Conclusion: Our findings showed statistically insignificant changes in the level of Caspase-cleaved- (M30) and uncleaved- (M65) cytokeratin 18 fragments (apoptotic and necrotic indicators, respectively) during neoadjuvant chemotherapy in patients with breast cancer. There was no notable relationship between tumor-related factors and either baseline levels or serum changes of CK18 fragments. Also, there was no correlation between M30/M65 level and pathologic response to neoadjuvant chemotherapy.